A pronounced evolutionary shift of the pseudoautosomal region boundary in house mice - White, Michael A. (2012)
The pseudoautosomal region (PAR) is essential for the accurate pairing and segregation of the X and Y chromosomes during meiosis. Despite its functional significance, the PAR shows substantial evolutionary divergence in structure and sequence between mammalian species. An instructive example of PAR evolution is the house mouse Mus musculus domesticus (represented by the C57BL/6J strain), which has the smallest PAR among those that have been mapped. In C57BL/6J, the PAR boundary is located just ~700 kb from the distal end of the X chromosome, whereas the boundary is found at a more proximal position in Mus spretus, a species that diverged from house mice 2–4 million years ago. Here, we use a combination of genetic and physical mapping to document a pronounced shift in the PAR boundary in a second house mouse subspecies, Mus musculus castaneus (represented by the CAST/EiJ strain), ~430 kb proximal of the M. m. domesticus boundary. We demonstrate molecular evolutionary consequences of this shift, including a marked lineage-specific increase in sequence divergence within Mid1, a gene that resides entirely within the M. m. castaneus PAR but straddles the boundary in other subspecies. Our results extend observations of structural divergence in the PAR to closely related subspecies, pointing to major evolutionary changes in this functionally important genomic region over a short time period.